2003
DOI: 10.1051/0004-6361:20030610
|View full text |Cite
|
Sign up to set email alerts
|

The composition of the interstellar medium towards the Lockman Hole

Abstract: Abstract. The Lockman Hole is well known as the region with the lowest neutral atomic hydrogen column density on the entire sky. We present an analysis of the soft X-ray background radiation towards the Lockman Hole using ROSAT all-sky survey data. This data is correlated with the Leiden/Dwingeloo survey (Galactic H  21 cm-line emission) in order to model the soft X-ray background by using radiative transfer calculations for four ROSAT energy bands simultaneously. It turns out, that an important gas fraction,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Weiß et al (1999) also found that IV21 contains two regions in different evolutionary states in the transition from atomic to molecular gas. There is also evidence that this cloud has an X-ray shadow against emission from the Galactic halo (Snowden et al 1994;Benjamin et al 1996;Kappes et al 2003), confirming that it is relatively local.…”
mentioning
confidence: 71%
“…Weiß et al (1999) also found that IV21 contains two regions in different evolutionary states in the transition from atomic to molecular gas. There is also evidence that this cloud has an X-ray shadow against emission from the Galactic halo (Snowden et al 1994;Benjamin et al 1996;Kappes et al 2003), confirming that it is relatively local.…”
mentioning
confidence: 71%
“…In addition, Kappes et al (2003) demonstrated that in the Lockman Hole region of the sky the halo is quite homogeneous. It is therefore probable that the Lockman observations were contaminated by solar protons or terrestrial CX emission.…”
Section: Non-shadowed Regionsmentioning
confidence: 99%
“…The equivalent kinetic energy of these eigenstates averaged over the electron and proton component is most simply calculated from 00 () 4 Ek   . The Milky Way exhibits a range of x-ray energies but the best estimates of the diffuse halo gas temperature are 6 1.3 1.5 10 K  (Kappes et al, 2003). If the hypothesis of energy transfer from dark to visible states is correct, one might expect to see, over a range of different halos, a linear correlation between two quantities 00 M R and the x-ray temperature, both of which should be measurable, the first by lensing and the second by x-ray satellites.…”
Section: Observations and Predictionsmentioning
confidence: 99%